Third Five Year Plan Orissa Programmes and Outlay - Planning Commission (Planning Commission, 1965)
Installation of the first 60 M. W. generating unit is expected to take place in 1964-65 and 1965-66 and the remaining three sets of 60 M. W. each in 1965-66. The 220 K. V. and 132 K. V. lines and Sub-stations would also be completed only in the 4th and 5th years of the Plan period. Programme of construction work For each principal component item of work, please state— (i) Dates of commencement and completion and phasing of programme by year, if possible—Commencement in 1961 and completion in fourth Plan.
Government of Orissa, Planning and Co-ordination, (Planning Department)